Stable vessel-cargo matching in dry bulk shipping market with price game mechanism. (November 2016) - Peng, Zixuan; Shan, Wenxuan; Guan, Feng; Yu, Bin
Highlights: A stable vessel-cargo matching model is proposed. A price game mechanism is designed for the disadvantaged participants. The matching equilibrium and price equilibrium are formulated. Three scenarios are discussed in the whole shipping cycle. Abstract: This paper proposes a model of stable vessel-cargo matching with price game mechanism in the dry bulk shipping market. The research aims at mimicking the bid of disadvantaged participants in the process of matching preferred objects. The matching equilibrium and price equilibrium are formulated between the shippers and carriers. A price game mechanism based Gale-Shapley algorithm is developed. Three scenarios of market dominated by shippers, market dominated by carriers, and equilibrium market are discussed in computational experiments. It is showed that if disadvantaged participants bid with the price game mechanism, they may gain more surpluses even in the negative position.